Effects of Oral Supplementation with Docosahexaenoic Acid (DHA) plus Antioxidants in Pseudoexfoliative Glaucoma: A 6-Month Open-Label Randomized Trial - Stéphanie Romeo Villadóniga; Elena Rodríguez García; Olatz Sagastagoia Epelde; M. Dolores Álvarez Díaz; Joan Carles Domingo Pedrol (Journal of Ophthalmology)
Purpose. To assess the effects of antioxidant oral supplementation based on docosahexaenoic acid (DHA) in pseudoexfoliative (PEX) glaucoma. Patients and Methods. A prospective 6-month open-label randomized controlled trial was conducted in patients with PEX glaucoma and adequate intraocular pressure (IOP) control. Patients in the DHA group received a high-rich DHA (1 g) nutraceutical formulation. Ophthalmological examination, DHA erythrocyte membrane content (% total fatty acids), plasma total antioxidant capacity (TAC), plasma malondialdehyde (MDA), and plasma IL-6 levels were assessed. Results. Forty-seven patients (DHA group 23, controls 24; mean age 70.3 years) were included. In the DHA group, the mean IOP in the right eye decreased from 14.7 [3.3] mmHg at baseline to 12.1 [1.5] mmHg at 6 months (P=0.01). In the left eye, IOP decreased from 15.1 [3.3] mmHg at baseline to 12.2 [2.4] mmHg at 6 months (P=0.007). DHA erythrocyte content increased in the DHA group, with significant differences versus controls at 3 months and 6 months (8.1% [0.9] vs. 4.4% [0.7]; P<0.0001). At 6 months and in the DHA group only, TAC levels as compared with baseline increased significantly (919.7 [117.9] vs. 856.9 [180.3] µM copper-reducing equivalents; P=0.01), and both MDA (4.4 [0.8] vs. 5.2 [1.1] nmol/mL; P  =  0.02) and IL-6 (2.8 [1.3] vs. 4.7 [2.3] pg/mL; P=0.006) levels were lower than in controls. Conclusions. Targeting pathophysiology mechanisms of PEX glaucoma by reducing oxidative stress and inflammation with a high-rich DHA supplement might be an attractive therapeutic approach. Despite the short duration of treatment, decrease in IOP supports the clinical significance of DHA supplementation.